Seroprevalence of Toxoplasma gondii and Cytomegalovirus in Aborted Women in Baghdad-Iraq - Gh. Al-Hindawi, Nada; A. Al-Shanawi, Fawzia (Iraqi Journal of Science, 2023)
Aim of this study was to assess the seroprevalence of Toxoplasmosis andCytomegalovirus (CMV) infection among aborted women. This study wasperformed on 282 aborted women and 50 normal pregnant women (control group)collected from Al-Yarmouk Teaching Hospital and Fatima Al-Zahraa Hospital forObstetrics and Children during October 2013 until the end of February 2014.Thesamples were tested with Latex Agglutination Test (LAT) and CMV Rapid TestCassette as a primary screening for T. gondii and CMV antibodies in the womensera. The primary tests showed a percentage of positive antibodies of T. gondii inaborted women and normal pregnant women 99(35.1%), 13(26%) respectively,while for CMV, it was 101(95.3%), 36(72%) respectively for the same groups,. Thesecond test used was Enzyme Linked Immuno-Sorbent Assay (ELISA) for thepositive sera in (LAT) test of T. gondii antibodies and for the positive sera incassette test of CMV antibodies. In this test, the women sera were divided into fourgroups: (IgG+ & IgM-), (IgG+ & IgM+), (IgG- & IgM+) and (IgG- & IgM-) forboth aborted and normal pregnant women, the results of T. gondii were: 73(73.7%),2(2%), 2(2%) and 22(22.3%) respectively compared with the control group13(100%) for the first group only, while the results of CMV were: 98(71.5%),0(0%), 2(2%) and 1(1%) respectively compared with the control group 35(97.2%)and 1(2.8%) for the first and second group respectively.